Social Space, Language, and Consciousness in Helena María Viramontes's Under the Feet of Jesus - Michael Nieto Garcia (Humaniora, 2004)
This paper analyzes social space with the tool of postmodern theories of space in the specific case of migrant agricultural workers portrayed in Helena María Viramontes's Under the Feet of Jesus. Language and consciousness are the main vehicles by which Estrella, the central protagonist of the novel, liberates herself from the dominant social discourses-linguistic, racial, economic, and gender-that position her as a neocolonial subject.